Allegro non troppo Bruno Bozzetto's Animated Music - Bellano, Marco (Animation: Key Films/Filmmakers, 2021)
"A film that will let you see the music and listen to drawings; in a word, a film full of Fantasia!" Bruno Bozzetto's Allegro non Troppo tips its hand right away: it is an unabashed, yet full of admiration, retake on Walt Disney's 1940 "concert feature". The obvious nod to that model fuels many tongue-in-cheek jokes in the film; however, Allegro non Troppo soon departs from mere parody, and becomes a showcase for the multifaceted aesthetics of Italian animation in 1976, as well as a witty social satire and a powerful rethinking of the music-image relationship in cinema. Marco Bellano's open access book reconstructs the history of the production of Allegro non Troppo, on the basis of an original research developed with the contribution of Bozzetto himself; it also presents an audiovisual analysis of the work, as to reassess the international relevance of Bozzetto's achievements by giving insight into the director's creative process. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.